2006
DOI: 10.1002/hyp.6284
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of evapotranspiration and its components from an apple orchard in northwest China using sap flow and water balance methods

Abstract: Abstract:Field experiments were conducted to investigate the effects of leaf area index and soil moisture content on evapotranspiration and its components within an apple orchard in northwest China for 2 years. Evapotranspiration in the non-rainfall period was estimated using two approaches: the soil water balance method based on tube-type time-domain reflection measurements, and sap flow plus micro-lysimeter methods. The two methods were in good agreement, with differences usually less than 10%. The component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 24 publications
3
36
5
2
Order By: Relevance
“…Gong et al () and Gong et al () measured transpiration and soil evaporation in apple orchards using sap flow and micro‐lysimeter methods, respectively, and found that sums of these measurements agreed well with estimates of ET obtained using the soil water balance method. In the two cited studies, ET values obtained using the soil water balance method were used as standards to assess the results of ET measurements by the sap flow and microlysimeter methods.…”
Section: Discussionmentioning
confidence: 91%
“…Gong et al () and Gong et al () measured transpiration and soil evaporation in apple orchards using sap flow and micro‐lysimeter methods, respectively, and found that sums of these measurements agreed well with estimates of ET obtained using the soil water balance method. In the two cited studies, ET values obtained using the soil water balance method were used as standards to assess the results of ET measurements by the sap flow and microlysimeter methods.…”
Section: Discussionmentioning
confidence: 91%
“…A key assumption of the T s -F v method is that λE is negatively correlated with temperature [2]. The dependence of λE on T s (or changes in Ts) is complicated because a series of processes are mixed together, i.e., the cooling effect of λE, thermal inertia changing with vegetation, soil moisture and soil texture, and impact of soil moisture, Ta and available energy on λE [26,27]. It is not surprise that Penman-Monteith algorithm, a robust physical theory, have a well performance.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of transpiration to total ET depends on vegetation coverage, surface wetness, and the availability of soil water for vegetation root transpiration uptake. When the surface is wet and vegetation coverage is low, soil evaporation tends to dominate [26]. The SGP is mainly covered by cropland and grassland ( Table 1).…”
Section: B Datamentioning
confidence: 98%
“…Embora existam dados de Kc para macieiras na literatura (ALLEN et al, 2006;GONG et al, 2007), nem sempre esses valores publicados se ajustam às condições locais (DRAGONI et al, 2004 Para o monitoramento hídrico do solo, foram empregados tensiômetros de punção instalados em duas profundidades, 10 e 30cm, entre três pares de plantas, correspondendo às camadas de 0 a 20cm e de 20 a 40cm, respectivamente. O intervalo de 0 a 40cm é onde se concentra a maior parte do sistema radicular da cultura (GREEN & CLOTHIER, 1999;HOFFMANN & BERNARDI, 2004), correspondendo à profundidade efetiva (PE) das raízes, que é o valor empregado nos cálculos de dimensionamento e manejo da irrigação.…”
unclassified
“…Os menores valores de ETc foram registrados no início e no final do ciclo da cultura (Figura 1), correspondendo aos períodos de início de crescimento dos frutos e início da hibernação, respectivamente. GONG et al (2007) registraram, na China, valor médio de ETc, igual a 2,2mm dia -1 , com um máximo de 4,4mm dia -1 , próximos aos observados no presente trabalho. GARCÍA-PETILLO et al (2003) Figura 2 -Coeficiente de cultura (Kc) para macieira cv.…”
unclassified